Introducing an attitude-based approach to emotional intelligence - Maddocks, Jo (Frontiers in Psychology, 2023)
Emotional intelligence (EI) was originally conceived as an ability, followed soon after by mixed, competency and trait theoretical models, broadly described as emotional efficacies (EE). Several models have attempted to integrate both approaches, with different views on whether EI and EE operate in sequence or parallel. One reason for this may be that EE constructs are given the same ontological status whether they represent underlying attitudes, such as self-regard, or behavioral competencies, such as assertiveness. In this paper, it is proposed that attitudes may predominantly act as underlying antecedents of ability-EI and behavioral-EE. Five benefits of this approach are drawn out that help to address some key concerns with current models and measures of EI and EE. First, the inclusion of implicit and explicit attitudes within integrated models of EI/EE would support the dual-processing of conscious and automated processes. From this, an attitude-based dual-processing framework for EI/EE is recommended. Second, the concept of Unconditional Positive Regard (UPR) for self and others (originally proposed by Carl Rogers, 1957), is identified as a potential attitude that may underpin the two core pillars of intrapersonal and interpersonal EI/EE. Third, UPR attitudes would provide an ethical basis for EI/EE that may support ethical and prosocial behavior. Fourth, UPR attitudes may differentiate between the optimal and sub-optimal elements of EI/EE. Fifth, an attitude-based approach to EI/EE may be more aligned with EI/EE being developmental than are the more static ability or trait-based models of EI/EE.